Performing Arts and Politics - vasinarom, manissa (King Prajadhipok’s Institute Journal, 2020)
This article aims to study the relationship between performing arts and politics,focusing on the influence of politics over changes in performing arts. The study is based on documentation, interviews, observation, and the researcher’s experience. The results show that performing arts are related to politics in six dimensions:meaning, form, content, function, core, and changing. Performing arts are meant to be a communication tool of leaders. They represent the identity and aspect of the art itself and the whole society. The format can be both simple and complex. The content is found to be both real society’s situation and imaginary to express, thoughts, feelings, and needs. The main idea generally presents leadership features,national situation, and government policies: concepts, practices, which can be admiration, obedience, and opposition to the current leader. This can be seen in literature and extemporaneous rhymes. The systemic changes of Performing Arts can be slow, steady, and violent. The political revolution severely affected leaders and Performing Arts, with the abolition of the old art and the creation of the new one to suit the taste and policies of the new leaders, in order to change the behavior, ideology, and values of individual and society as they expect. This phenomenon can occur for a period of time or has an effect in the long run. However, the situation will be reversed when social crises lead to the revolution and the next cycle continues.